COMPOSITION AND ZOOGEOGRAPHICAL DISTRIBUTION OF MAMMALS OF THE CAUCASUS - A. M. Batchiev (Юг России: экология, развитие, 2014)
Abstract. Subject, theme, aim of the work. The Caucasus is a mountainous country with very rich natural environment, which defines a large variety of wildlife in the region, the complexity of its fauna. On this basis, the aim of the work was to study the composition of each mammal species fauna and selection on this basis mammals of the Caucasus, the structure of each species area and selection on this basis the ecological and faunal groups, types of mammalian fauna of the Caucasus, in the integration of them in zoogeographical complexes. It was made the attempt to conduct an objective zoogeographical analysis of Caucasus theriofauna at the present material.Methods. The main research method was a zoogeographical method. We studied the composition, distribution of Caucasus theriofauna species, determined the habitat optimum and the geometric center of the area, the ecological specificity of each species, and its compliance with the optimum selected habitat conditions. On this basis and taking into account the history of the fauna formation and its genetic makeup, we distinguished the ecological faunal groups that served as the basis for the allocation of fauna types and combining them into zoogeographical complexes.Results. It has been identified a total species composition and it has been obtained an objective picture of the Caucasus mammals distribution on the established ecological and faunal groups on the basis of the environmental features analysis of the species needs, revealing their locations and the optimum concentration of population in the area of distribution. Three new ecological and faunal groups of mammals has been proposed to use in the Caucasus, one of which is a Caucasian mountain-steppe, for the first time. The list of endemic and relict theriofauna of the Caucasus has been defined. The basis for a complete analysis of theriofauna zoogeographical region has been prepared. The area of results application. The obtained results allow us to identify and clarify the naturally existing in the course of historical development the modern faunal connections, patterns of the Caucasus theriofauna genesis. This information makes it possible in the future, taking into account the results of our other work, to make theriofauna zoogeographical analysis, to suggest certain additions and clarifications to the zoogeographical regionalization of the Caucasus, to organize continuous monitoring of the species condition associated with increased activity of human impact on the landscape of the Caucasus.Summary. As a result of this work, it has been revealed dwelling in the Caucasus region up to 156 species of mammals, it has been studied their distribution both within the Caucasus and throughout the whole territory of residence and the structure of their areas. On this basis, it has been allocated up to 16 ecological and faunal groups and it has been presented their zoogeographical range. It has been made the basis for a complete analysis of the Caucasus zoogeographical theriofauna.